Parameter estimation for a discrete time model driven by fractional Poisson process. Issue 10 (19th May 2023) - Araya, Héctor; Bahamonde, Natalia; Roa, Tania; Torres, Soledad
Abstract: In this article, we study the parametric problem of estimating the coefficient for a discrete time model driven by a fractional Poisson noise, when high-frequency observations are given. We consider weighted least squares and maximum likelihood estimators. Thus, asymptotic behavior of the estimators is proved and a simulation study is shown to illustrate our results.